Metode RGEC: Penilaian Tingkat Kesehatan Bank Sebelum dan Sesudah Merger Menjadi Bank Syariah Indonesia - Siti Rahma Putri; Linda Rahmazaniati (Akbis: Media Riset Akuntansi dan Bisnis, 2022)
This study aims to understand the soundness of Islamic banks in Indonesia by using the RGEC method as set out in Bank Indonesia Regulation PBI No. 13/l/PBI/20ll. The assessment factors in the RGEC method are Risk Profile, GCG (Good Corporate Governance), Capital (Capital) and Profitability (Earnings). The subjects of this research are all companies belonging to Islamic banking listed on the Indonesia Stock Exchange for the period 2020-2021. The sampling technique used a purposive experiment. The audit strategy used is descriptive quantitative by ensuring the monetary proportion using the RGEC strategy. The consequences of this study prove that a bank that has a very healthy level of health category for the 2020 period is Bank Syariah Mandiri, while in 2021 the health level that is in the healthy category is BSI (Bank Syariah Indonesia).